2020
DOI: 10.1021/acs.langmuir.0c02457
|View full text |Cite
|
Sign up to set email alerts
|

Salting Up and Salting Down of Bovine Serum Albumin Layers at the Air–Water Interface

Abstract: The surface adsorption of bovine serum albumin in pure water and salted aqueous solutions was studied by neutron reflection. With the contrast match technique, the surface excess in null reflecting water as a function of the protein concentration was revealed. It is found that, in a concentration range from 1 ppm (parts per million, mg/L) to 1000 ppm, without salts, the surface excess shows a profound peak at around 20 ppm; with salts, the surface excess increases steadily with the protein concentration. When … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“…In fact, Herboth et al used molecular dynamics simulations to show that phenylalanine (Phe) and valine (Val) have greater affinity for the interface at low pH, while glycine (Gly) did not . It has also been shown that salts can drive proteins to or away from the air–water interface. Determining whether AAs reside at SSA interfaces is important because the surface of an aerosol impacts its properties of water uptake, morphology, and heterogeneous chemical transformations. It is also essential to determine the behavior of AAs and peptides in aerosols as they are used in food and medicine, including trileucine as a medicinal aerosol dispersibility enhancer …”
mentioning
confidence: 99%
“…In fact, Herboth et al used molecular dynamics simulations to show that phenylalanine (Phe) and valine (Val) have greater affinity for the interface at low pH, while glycine (Gly) did not . It has also been shown that salts can drive proteins to or away from the air–water interface. Determining whether AAs reside at SSA interfaces is important because the surface of an aerosol impacts its properties of water uptake, morphology, and heterogeneous chemical transformations. It is also essential to determine the behavior of AAs and peptides in aerosols as they are used in food and medicine, including trileucine as a medicinal aerosol dispersibility enhancer …”
mentioning
confidence: 99%
“…What's more, the FRR of the electroneutral membrane is 95.2% when circulating BSA fouling and water cleaning twice, which is significantly higher than those of negatively and positively charged membranes (Figure 4D). Considering the BSA solution is weakly negative-charged since its isoelectric point is 4.8, 50,51 the improved anti-fouling characteristics of electroneutral membranes should arise from the smoother surface than negatively charged membranes and charge-shielding effect (Figure 4E). It is worth noting that the PWP decreases with further increased amination (14 wt% TETA) because of increased cross-linking degree (Figure S11).…”
Section: Anti-fouling Property Of Electroneutral Nf Membranesmentioning
confidence: 99%
“…BSA is our proxy-protein of choice because of the abundance of previous literature investigations indicating that there is a plethora of proteins and amino acids in the ocean. BSA is frequently used in the literature as a proxy-protein for surface studies because BSA captures slow adsorption commonly observed within the air–ocean surface. While it does not completely capture the nuance of the ocean surface chemistry, the literature results and precedence strongly suggest that it is a suitable proxy for understanding fundamental adsorption changes.…”
Section: Introductionmentioning
confidence: 99%